Revision of the spider genus Caloctenus Keyserling, 1877 (Araneae, Ctenidae - Silva-Dávila, Diana (2004)
Caloctenus Keyserling is examined and redefined to include small ground-dwelling spiders with an enhanced ventral spination beneath anterior tibiae/metatarsi -a combination of five-eight/six-seven paired-spines, pars cephalica well marked by a deep furrow, strongly convex pars thoracica, and body thickly coated with iridescent scales. As relimited, Caloctenus comprises four species from northern South America; a key to identify them is provided. Males of C. aculeatus Keyserling and C. gracilitarsis Simon are described for the first time, as are two new species, C. carbonera from Venezuela, and C. oxapampa from Peru. All other species described under this genus belong somewhere else. Caloctenus boetonensis Strand, C. celer Simon, and C. oreus Simon are transferred to Acantheis Thorell, 1891. Caloctenus fernandensis Simon is transferred to Africactenus Hyatt, 1954. Caloctenus penicilliger Simon and C. variegatus Bertkau are transferred to Enoploctenus Simon,1897. Caloctenus abyssinicus Strand is placed incertae sedis within Ctenidae.